Pengaruh Service Excellence, Aksesibilitas, dan Word of Mouth (WOM) terhadap Minat Wisatawan serta Implikasinya terhadap Keputusan Kunjungan Wisata Halal di Kabupaten Bandung Barat - Kartika Dewi; Imam Sudirman; Rian Andriani (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
This research was conducted at the Halal Tourism object, West Bandung Regency. The research method used in the study uses quantitative methods with the testing tool using the Smart-PLS tool, with a sample of 100 respondents. Based on the results of the study, the direct influence of Service Excellence on tourist interest is 4%, Accessibility to tourist interest is 0.5%, Word of Mouth to tourist interest is 45%, Tourist Interest is 74.9%. The simultaneous influence of Service Excellence, Accessibility, and Word of Mouth on Tourist Interest in West Bandung Regency is 56.3%. The influence of tourist interest on the decision to visit Halal tourism in West Bandung Regency is 74.9%.